(untitled) (Revista de Estudos da Linguagem, 2018)
Abstract: The article aims at better understanding the usage of Lithuanian and Brazilian masculine first names by means of an exploratory comparative study based on statistical sources from national institutional websites of Lithuania and Brazil. Even though the two countries are rather different in terms of geography, number of population and official languages, there are some overlapping points along their history which suggest that the repertoire of names, particularly masculine ones, may have some similarities. The research results have confirmed the existence of equivalent names in both countries. These names are Christian names and their usage is influenced by Catholicism, a dominating religion in both countries. However, there is no evidence that names in different languages, that are equivalent in form and origin, should also have equivalent connotations. Keywords: Onomastics; Anthroponomy; Comparative Anthroponomastics. Resumo: Este artigo objetiva compreender melhor os usos de prenomes masculinos na Lituânia e no Brasil mediante um estudo exploratório comparativo baseado em dados estatísticos disponíveis em sites institucionais de cada país. Apesar das diferenças geográficas, populacionais, e linguísticas existentes, há pontos de contato ao longo da História desses países o que sugere a possibilidade de haver alguma convergência nos repertórios de nomes de pessoas utilizados, especialmente no que tange os nomes masculinos. Os resultados da pesquisa confirmaram a existência de nomes equivalentes em ambos os países. São nomes cristãos cujo uso foi influenciado pelo Catolicismo, religião predominante nos dois países. Contudo, não há evidência de que nomes em línguas diferentes que se equivalem formalmente e do ponto de vista de sua origem, também apresentem conotações equivalentes. Palavras-chave: Onomástica; Antroponímia; Antroponomástica Comparada.